Economic Effect of Plant Growth Regulator in the Landscape Maintenance - Velasco O., Jose E. (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The green industry is an important contributor for the US economy and among all the sectors Landscape services is the most important segment in sales, employment and business taxes (Hodges, Hall, Palma, & Khachatryan, 2015). It gives more than1.1 Million jobs and over USD 80 Billion revenues. It is the fastest growing sector. Landscape and horticulture provide labor-intensive services (pruning, mowing, weeding, etc.). Landscape services are more dependent on labor than other segments, in addition seasonality of services, increasing wages and tight labor market threaten the industry´s profit. New technologies, such as Plant Growth Regulator (PGR´s), are used to work on these issues; they are used to improve the quality and speed of manual labor and reduce labor costs and improve productivity. This study provides information to understand if the extra cost of using PGR´s is justified by the reduction of labor needed. Economic analysis such as a partial budget analysis and sensitivity analysis where done to evaluate the benefits of using PGR´s in the landscape industry. It was found that PGR´s can reduce labor needs due to lower shrub and lower pruning needs, in the study was found that the pruning time was reduced from 83 to 97%. Labor availability and increasing wages can increasingly impact labor savings due to PGRs.